(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to increase the capacity of local communities to develop entrepreneurship based on local agricultural wisdom in Entubuk Village, Sekadau Regency. This village has a strong agricultural tradition but faces challenges such as low product value, limited processing skills, and limited market access. The program applies an Asset-Based Community Development (ABCD) approach, including training in entrepreneurship, financial management, hygienic production, branding, and digital marketing, as well as product prototyping and market testing. The results show an increase in community knowledge and skills, the formation of business groups with clear roles and standard operating procedures, and the development of value-added products such as premium rice, spiced tea, and cassava-based products. The program also initiated offline and digital marketing channels. These findings indicate that entrepreneurship based on local wisdom can effectively strengthen economic resilience while preserving cultural identity in rural communities.